Students’ Difficulties in Learning Poetry at Faculty of Cultural Science of Mulawarman University Academic Years 2017/2018 - Eliasari Eliasari (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2018)
The study intended to find out students’ difficulties and the factors influencing learning poetry. The researcher tried to find the difficulties that affected the students at the Faculty of Cultural Science Mulawarman University during the learning process. The student's difficulties in learning caused by many factors, such as the facility as assisted learning, the materials or textbook, teaching methods, learning resources, and from the students themselves. The design of this study was descriptive quantitative. It conducted to determine the value of independent variables without making a comparison with other variables. The population of the study was English literature students in the academic year 2017/2018. The researcher took 50 students from the population as samples in this study. The data of this study were collected by using the checklist questionnaire and interview. Based on the result of this study, it was found that the students were having difficulties in understanding the figurative languages, analyzing the words and elements, interpreting the meaning of the poem, reciting and writing the poem. The difficulties were faced by the students in learning poetry influenced by several factors. They were the difficulties in students’ literary competence (23%), teaching methods (21%), students’ references (20%), learning resources (19%), and the learning materials or textbooks (17%). To summarize this study appeared to claim that the English literature students were having difficulties and influenced by several factors in learning poetry. This study intended to examine the difficulties and the factors that influenced the students as a consideration to determine an effective teaching and learning poetry.